Rekonstruksi pendidikan anak dalam Islam di Era 5.0: Studi integrasi pemikiran Buya Hamka dan M. Quraish Shihab - Purnomo, Sutrimo; Sumiarti (Yinyang: Jurnal Studi Islam Gender dan Anak, 2023)
The era of 5.0 has had an impact that is not entirely good, even advances in information and technology have become one of the causes of moral degradation in children. If this is allowed to continue, a younger generation will emerge who are intellectually superior but weak morally. This is at the same time an indicator of the failure of the world of education, because the ultimate goal of education is to create a moral generation. For this reason, efforts to anticipate moral degradation in children as a result of the 5.0 era must be carried out, including through the reconstruction of children's education in Islam. This study aims to offer readers a formulation of children's education in Islam in the era of society 5.0 through the integration of the thoughts of two Indonesian Muslim scholars, namely M. Quraish Shihab and Buya Hamka. This research is a qualitative research type which is library research by making a systematic review as a research approach. The findings illustrate that children's education in Islam in the 5.0 era can be done through four things, namely: First, strengthening the goal of creating humans as servants. Second, the strengthening of gratitude which is implemented in the spirit of talabul 'ilmi. Third, aqidah or monotheism education about the Oneness of Allah must be instilled from an early age. Fourth, the cultivation of good morals, especially devotion to parents and also to others and the environment, is used as the direction of children's education in Islam.